Cuprate-like electronic properties in superlattices with AgIIF2 square sheet - Yang, Xiaoping (2014)
Using the generalized gradient approximation augmented with maximally localized Wannier functions analysis, we present the formation of cuprate-like electronic structures in AgIIF2–related superlattices resulted from the confinement together with structural chemical modification. The out–of–plane electronic reconstruction leads to electron doping of AgF2 plane and gradually destablizes the antiferromagnetic state. Eventually a stable nonmagnetic metallic state emerges by applying in–plane tensile strain, in which the shape of effective Fermi surface of AgF2 plane exhibits the key feature of high–temperature cuprate superconductor.